Does COVID-19 infection impact on the trend of seasonal influenza infection? 11 countries and regions, from 2014 to 2020 (2020)
Objectives: Infection due to the 2019 novel coronavirus disease (COVID-19) is dramatically widespread around the world. The COVID-19 pandemic could increase public concern to prevent infectious disease. The present study aimed to assess the relationship between the COVID-19 epidemic and the potential decrease in seasonal influenza cases. Methods: This study was performed to show trends in seasonal influenza cases from the 2014–2015 season to the 2019–2020 season in 11 countries and regions, and evaluate whether the trends in the 2019–2020 season were different before and after the COVID-19 pandemic compared to previous seasons using a quasi-experimental difference-in-difference design. Results: In East Asia, the number of seasonal influenza cases in the 2019–20 season was lower after the COVID-19 transmission compared to previous years. However, this was not the case in American countries or in European countries. Conclusion: The COVID-19 epidemic might have altered health behaviors, resulting in an unexpected reduction of seasonal influenza cases.